Examining the Discourse of Perfume Advertisements: An Analysis of the Verbal and the Visual - Lunyal, Vandana (Journal of NELTA, 2015)
In the world that promotes consumerism, companies are in a competition to produce a variety of commodities and to convert people into consumers of their products whether they need them or not. The abundance of consumer products is promoted through advertisements. These advertisements persuade the common people to become consumers for which they use a variety of strategies, the most common being the use of problem-solution format in language and an effective use of the verbal and the non-verbal. This paper focuses on investigating the verbal and the non-verbal aspects of the text to examine how ideological constructs function in the discourse of advertisingthrough the use of hegemony. A perfume advertisement has been selected for a detailed analysis of the verbal and the visual elements to illustrate how advertisers commonly attempt to transmit some underlying, yet unasserted, meanings to unsuspecting readers who may understand the intentions of the advertisers i.e. to promote consumption but may not understand that the aim is achieved by generally promoting cultural stereotypes which work towards the disadvantage of one social group vis-à-vis the other especially the one that the advertisement is addressed to. The tool for the analysis of the advertisement is Fairclough’s model of critical discourse analysis (CDA) that uses the analysis of the verbal and the visual to reveal ideological underpinnings. CDA also has pedagogical implications for instance the language used for describing products, if analysed critically by language learners, helps them to unfold the hidden meanings as is illustrated through the analysis. DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12085 Journal of NELTA, Vol 19 No. 1-2, December 2014: 117-131